The Role of Health-promoting Lifestyle in Predicting Cognitive Status of Older Clergymen - Shahab Papi; Nasibeh Zanjari; Zeinab Karimi; Seied Vahid Motamedi; Reza Fadayevatan (University of Social Welfare & Rehabilitation Sciences, 2021)
Objectives: Healthy lifestyle along with spirituality affect the physical and mental health of older adults. Regarding the older clergymen's experience of spiritual life, this study aims to evaluate the role of health-promoting lifestyle in predicting cognitive status of older clergymen.  Methods & Materials: This cross-sectional study was conducted on 190 older clergymen living in Qom, Iran who were selected using a convenience sampling method and based on the inclusion/exclusion criteria. Health Promoting Lifestyle Profile II and Mini-Mental State Exam were used to collect data. The collected data were analyzed in SPSS V. 22 software using descriptive and inferential statistics (Correlation test, linear regression analysis, independent t-test, and ANOVA). The significance level was set at 0.05. Results: The mean age of participants was 70.55±6.86. There was a significant positive relationship between health-promoting lifestyle and cognitive status (r= 0.295, P= 0.001). The results of multiple regression analysis showed that the dimensions of health responsibility and nutrition along with employment status explained almost 14% of the variance in cognitive status. Conclusion: it is necessary to pay more attention to nutrition and health responsibility in health-promoting interventions of older clergymen. Further studies with a qualitative approach are recommended to understand the mechanism of the effect of spirituality on health of older clergymen.